Pendampingan Penerapan Metode Tahsin Di Majelis Ta’lim Khairunnisa Kavling Polri Ragunan - Fatimah, Fatimah; Wahyuni, Sri; Sulasmi, Andi (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
The purpose of this community service is to provide socialization and assistance regarding the application of the tahsin method to improve the ability to read the Qur'an with proper tajwid and makharijul huruf. This Community Service (PkM) was carried out at the Majelis Ta'lim Khairunnisa Kavling Polri Ragunan. The method of implementing community service, among others: 1) Observation stage, at this stage the PkM implementing team conducted observations at the Majelis Ta'lim. The PkM team asked permission from the head of the majelis ta'lim, determined the schedule and discussed the appropriate material or theme of service and the facilities to be used, 2) Planning stage, at this stage the PkM team provided supplies and prepared a PkM proposal, 3) Preparation stage, at this stage the PkM Team communicated again with the majelis ta'lim to determine the number of participants, place and method of socialization, 4) Implementation stage, at this stage the PkM activities took place, namely presentation and practice (mentoring), the next activity was a discussion or question and answer session related to the material, and continued with an evaluation. The results achieved in this community service are: 1) members of the Khaitunnisa Ta'lim Assembly in the Ragunan Police Station (Kavling Polri) have learned and understood the tahsin method; 2) members of the Ta'lim Assembly have improved their ability to read the Quran well, thus producing Qur'anic individuals who are not only able to read but also understand and apply its contents in their daily lives; and 3) publication of articles in journals.